2021
DOI: 10.48550/arxiv.2109.12794
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spin-singlet and spin-triplet pairing correlations in antiferromagnetically coupled Kondo systems

Abstract: Recent experiments in quantum critical heavy fermion metals have pushed to the fore the question about whether antiferromagnetic fluctuations can promote both spin-singlet and spin-triplet superconductivity. Here we address the issue through non-perturbative calculations in antiferromagnetically correlated Kondo systems. We identify Kondo-destruction quantum critical points in both the SU(2) symmetric and Ising-anisotropic cluster Bose-Fermi Anderson models. The spin-singlet pairing correlations are significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…So let us make a few points clear. First, even if ferromagnetic fluctuations would certainly favour spin triplet pairing, spin triplet superconductivity can also arise without ferromagnetic fluctuations; this possibility has even been predicted long ago [138], and continues to stimulate theoretical work (see [139] for a quite recent example, referring also to UTe 2 ). Experimentally, a good example is UPt 3 , where ferromagnetic excitations have never been observed [140].…”
Section: T Sc (K)mentioning
confidence: 99%
“…So let us make a few points clear. First, even if ferromagnetic fluctuations would certainly favour spin triplet pairing, spin triplet superconductivity can also arise without ferromagnetic fluctuations; this possibility has even been predicted long ago [138], and continues to stimulate theoretical work (see [139] for a quite recent example, referring also to UTe 2 ). Experimentally, a good example is UPt 3 , where ferromagnetic excitations have never been observed [140].…”
Section: T Sc (K)mentioning
confidence: 99%
“…Taken together, these experiments (Schuberth et al, 2016;Nguyen et al, 2021) provide compelling evidence that superconductivity is driven by the KD quantum criticality. Moreover, the high-field superconducting phase was tentatively identified as a potential case of spin-triplet pairing (Nguyen et al, 2021), a result that is supported by the calculations of pairing correlations near the KD QCP of a cluster Bose-Fermi Kondo model in the Ising-anisotropic case (Pixley et al, 2015;Hu et al, 2021b), especially when the Zeeman effect of the external magnetic field is considered (Hu et al, 2021b).…”
Section: Survey Of Hf Systems With Multiple Superconducting Phasesmentioning
confidence: 65%
“…Even when SOC is not dominant, it can lead to a coupling between the orbital and spin DOF of the pairing state leading to nontrivial structure for given spin-singlet or -triplet configurations, as proposed for UTe 2 (Chen et al, 2021). Furthermore, an Ising anisotropy of the RKKY interactions due to SOC, can also make spin-triplet pairing states competitive, even in the nominally AFM case (Hu et al, 2021b). While on the topic of the interplay between orbital and spin DOFs, as promoting pairing states with novel properties, we briefly mention that it can also be central to the important family of the ruthenates.…”
Section: Discussionmentioning
confidence: 98%
“…While this would not have been a surprise had the quantum criticality been of nearly ferromagnetic (and conventional) type [66], how could spin-triplet pairing develop for Kondodestroying type AF quantum criticality as is the case in YbRh 2 Si 2 ? Insights into this question have come from theoretical studies near a Kondo-destroying QCP in antiferromagnetically coupled Kondo models [67]: They showed that significant Ising anisotropy, as it effectively arises under an external magnetic field in the easy-plane antiferromagnetically correlated YbRh 2 Si 2 , makes the spin-triplet pairing competitive.…”
Section: Nucleation and Percolation Of Superconductivitymentioning
confidence: 99%